Acquired vancomycin resistance in clinically relevant pathogens. (October 2008) - Werner, Guido; Strommenger, Birgit; Witte, Wolfgang
Acquired resistance to vancomycin is an increasing problem in pathogenic bacteria. It is best studied and most prevalent among Enterococcus and still remains rare in other pathogenic bacteria. Different genotypes of vancomycin resistance, vanA –– G, have been described. The different van gene clusters consist of up to nine genes encoding proteins of different functions; their interplay leads to an alternative cell wall precursor less susceptible to glycopeptide binding. Variants of vanA and vanB types are found worldwide, with vanA predominating; their reservoir is Enterococcus faecium . Within this species a subpopulation of hospital-adapted types exists that acquired van gene clusters and which is responsible for outbreaks of vancomycin-resistant enterococci all over the world. Acquisition of vanA by methicillin-resistant Staphylococcus aureus (MRSA) is worrisome and seven cases have been described. Nonsusceptibility to glycopeptides also occurs independently from van genes and is a growing therapeutic challenge, especially in MRSA.